2001
DOI: 10.1094/mpmi.2001.14.8.969
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine-1-Carboxamide Production in the Biocontrol Strain Pseudomonas chlororaphis PCL1391 Is Regulated by Multiple Factors Secreted into the Growth Medium

Abstract: Pseudomonas chlororaphis PCL1391 controls tomato foot and root rot caused by Fusarium oxysporum f. sp. radicis-lycopersici. The production of phenazine-1-carboxamide (PCN) is crucial for this biocontrol activity. In vitro production of PCN is observed only at high-population densities, suggesting that production is under the regulation of quorum sensing. The main autoinducer molecule produced by PCL1391 was identified structurally as N-hexanoyl-L-homoserine lactone (C6-HSL). The two other autoinducers that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 40 publications
(49 reference statements)
2
90
0
2
Order By: Relevance
“…Under various growth conditions the amounts of C 6 -HSL present in PCL1391 spent culture medium were shown to be correlated with the amounts of PCN produced (Chin-A-Woeng et al, 2001bvan Rij et al, 2004). In our study, the correlation of PCN and C 6 -HSL levels among the various PCL1391 derivatives (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under various growth conditions the amounts of C 6 -HSL present in PCL1391 spent culture medium were shown to be correlated with the amounts of PCN produced (Chin-A-Woeng et al, 2001bvan Rij et al, 2004). In our study, the correlation of PCN and C 6 -HSL levels among the various PCL1391 derivatives (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing showed that this fragment shared high homologies (see Results) with rpoS genes of other Pseudomonas strains. Subsequently, primers oMP770 and oMP771 were designed based on the partial rpoS sequence and used in PCR on a pBlueScript chromosomal library of PCL1391 (Chin-A-Woeng et al, 2001b) in combination with oMP49 and oMP50, which anneal close to the multi-cloning site of pBlueScript. oMP770 in combination with oMP49 produced a fragment of 1?2 kb containing the flanking region upstream of rpoS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11) When AHL concentrations increase and reach a threshold, AHL receptor proteins belonging to the LuxR protein family bind AHL and regulate the expression of numerous genes. AHL-mediated quorum sensing regulates various phenotypes in plants, including the production of exoenzymes 12) and antimicrobial substances, 13) motility, 14−15) biofilm formation, 16) epiphytic fitness, 17) and pathogenicity. 12,18) Although many AHL-producing bacteria have been isolated from the phyllosphere, 4−7) the role of quorum sensing in adaptation to survival on the plant surface and its contribution to shaping certain community structures has not yet been elucidated.…”
mentioning
confidence: 99%